Effect of pharmacist led intervention on health related quality of life in diabetic patients assessed using EQ5D domains and visual analogue scale - Muhammad Zahid Iqbal; Saad S. Alqahtani (Scientific Reports)
Abstract Diabetes-a life style based chronic metabolic disease if left untreated and unmanaged can lead to various complications among diabetics. To improve the health-related quality of life of diabetics, health care providers are classically placed to present suitable interventions. The objective of the present study was to evaluate the effect of pharmacist-led educational intervention on the diabetic patient-reported quality of life upon all the domains of EQ-5D. The study subjects selected for the present study were divided among two equal study arms after being recruited from the hospitals randomly. The controlled group consisted of 200 diabetic patients getting regular treatment from the hospitals. Whereas, the interventional group comprised of those 200 diabetic patients who were receiving the pharmacist collaborative care from DMTAC clinics along with the routine diabetic management and treatment. The study duration was of 1 year and consisted of two follow up visits for both study arms. A generic health related quality of life tool EQ-5D was used for exploring and examining the study data. However, to determine the setbacks in all the individual EQ-5D domains and VAS average scores involving ANOVA and T test analysis have been used. The mean glycated haemoglobin-HbA1c was decreased to 1.44% in control group, whereas, a decrease of 2.84% was seen in interventional study arm. A statistically significant betterment in glycated haemoglobin level was seen in the interventional study arm i.e., p < 0.05. However, all the domains of the questionnaire-EQ-5D 5 L conferred significant association with the health related quality of life parameters (p < 0.05). Moreover, in control study arm a statistically significant enhancement is seen related to average scores of health related quality of life reported by patients on the Visual Analogue Scale (VAS) from 55.89 ± 7.52 to 64.86 ± 5.04. Moreover, the average scores have been ranged from 54.45 ± 8.81 to 72.23 ± 6.41 among interventional study arm, presenting the statistically significant values i.e., F statistics 118.67 (1, 292) along with p < 0.001. The effect of pharmacist involvement in the form of intervention provision presented a positive improvement and statistically significant enhancement on every domain of the questionnaire-EQ-5D. The pharmacist collaborative care in the form of intervention turned out effective in enhancing the patient reported quality of life as well as in improving glycated haemoglobin (HbA1c) levels.